The impact of mangrove damage on tidal flooding in the subdistrict of Tugu, Semarang, Central Java - Westi Utami; Yuli Ardianto Wibowo; Ahmad Haris Hadi; Fajar Buyung Permadi (Journal of Degraded and Mining Lands Management, 2021)
Expansion of industrial areas, aquaculture, settlements, and limited knowledge of the community about the function of mangroves allegedly led to the conversion of mangrove functions in the early 1990s. This study aimed to map the condition of mangroves from 1988, 1990, 1995, 2008, to 2021 and their effect on the widespread of tidal flooding in three villages (Mangkang Kulon, Mangunharjo, Mangkang Wetan) in Tugu subdistrict, Semarang City. The research method was carried out by using spatiotemporal analysis of Landsat 5 and Landsat 8 imagery through the supervised approach (Maximum Likelihood algorithm). In order to map the correlation of mangrove damage with the widespread impact of tidal flooding, an overlay analysis of land use maps was carried out in 1988, 1990, 1995, 2008 and 2021. The results of the study showed that mangrove damage is correlated with the widespread of tidal flooding that drowns settlements, ponds, and agricultural land. Data analysis showed that the mangrove area in three villages has decreased from 1988 to 2021, covering an area of 242.66 ha. This condition is one of the triggers for the increase in tidal flooding area from 1988 to 2021, covering an area of 253.135 ha. As a natural barrier to prevent abrasion and tidal flooding, mangrove conservation is very necessary, considering the impact of tidal flooding on the coast of Semarang City is increasingly widespread.